LIVERPOOL WEB DEVELOPMENT BY USING THE FOOTBALL CLUB MacroMedia Flash 5.0 - Dhani Saputra (Jurnal Manajemen Informatika, 2010)
Along with the development of the age of information technology particularly in the technologyworld that use computers are very fast, in the field of the homepage is one of the mostdeveloped part of the Internet as new media in the electronic publication of informationpresented and can be seen by millions of people around the world.In making theWeb Liverpool Football Club is the author put on an animated web site that usesMacromedia Flash 5.0 programming language, a new program to exploit its superiority in termsof animation on a web site that is ActionScript inside to run the animation.